The Naiṣkarmya siddhi of Sureśvarācārya : with the Candrikā of Jñānottama ; edited with notes and index by G.A. Jacob ; revised edition with introduction and explanatory notes by M. Hiriyanna - Sureśvarācārya (SAMP early 20th-century Indian books project, 1925)
Compendium of Advaita Vedanta, with Naiṣkarmyasiddhicandrikā Sanskrit commentary of Jñānottama Miśra.